Performance comparison of position-based routing protocols in the context of solving greedy failure - Al-shugran, Mahmoud; Ghazali, Osman; Hassan, Suhaidi (2012)
In Mobile Ad-hoc Networks (MANETs), greedy forwarding strategy (GFS) seems to be the method of choice for position-based routing protocols. During the last decade GFS has become the subject of research.However, with greedy routing there is no guarantee that a node could always find a suitable next-relay hop to forward its packet. Of such situation, forwarded packets might be ends at a concave (Hole) node that result in the forwarded packet to be dropped.This "Hole" node might be out of battery power, full congested or does not have neighbor(s) in the direction of ultimate destination, etc. Accordingly, this Hole is considered as vital section of the whole network which results that the whole MANET fails. Considering the problem of greedy failure at the network holes, several works have been proposed in the state. In this paper, we present these works in new classification with two categories. Moreover, an investigation of the proposed routing protocols corresponding to each category is conducted.Thus, besides the new classification, this paper presents an overview and a qualitative comparison of the existing position based routing protocols that tried to solve greedy failure. The noble goal of this classification and investigation is to conclude the most important features to be considered in rebuilding GFS to make it as standalone position based routing protocol.As future research efforts.Hopefully that GFS with the new features becomes more reliable and efficient that satisfies most MANET's applications.